Miniaturized microstrip bandpass filter based on adjacent-nonadjacent coupling - Rao Xiaohong; Ni Piao; Jin Haiyan; Huang Tao; Huang Yongmao (Dianzi Jishu Yingyong, 2018)
A miniaturized microstrip bandpass filter is presented. The proposed filter consists of four folded stepped-impedance resonators. As compared with its corresponding conventional uniform-impedance resonator or stepped-impedance resonator counterparts, the folded stepped-impedance resonator can save nearly 50% circuit size since it takes full advantage of its occupied circuit area. Owing to the simultaneous existence of the adjacent and nonadjacent coupling in the proposed bandpass filter, three different cross-coupling path-pairs can be established to generate three different transmission zeros, which can improve the selectivity performance and width of stopband of the proposed filter effectively. Measured results of the prototyped filter agree with its simulations quite well. Meanwhile, the prototyped filter performs roll-off speed of 100 dB/GHz, and its upper stopband can be up to 11.5 GHz with relative rejection over 33 dBc. Compared with some similar works, the prototyped filter achieves electrical-size-reduction of 23%, which can satisfy the requirements of miniaturization of microwave circuits.